Myoendothelial Junctions of Mature Coronary Vessels Express Notch Signaling Proteins - McCallinhart, Patricia E.; Biwer, Lauren A.; Clark, Olivia E.; Isakson, Brant E.; Lilly, Brenda; Trask, Aaron J. (Frontiers in Physiology, 2020)
Rationale: Myoendothelial junctions (MEJs) within the fenestrae of the internal elastic lamina (IEL) are critical sites that allow for EC-VSMC contact and communication. Vascular Notch signaling is a critical determinant of normal vasculogenesis and remodeling, and it regulates cell phenotype via contact between endothelial cells (ECs) and vascular smooth muscle cells (VSMCs). To date, no studies have linked Notch signaling to the MEJ despite it requiring cell-cell contact. Furthermore, very little is known about Notch in the adult coronary circulation or the localization of Notch signaling and activity within the mature intact blood vessel. Objective: We tested the hypothesis that vascular Notch signaling between ECs and VSMCs occurs at MEJs. Methods and Results: Notch receptor and ligand immunofluorescence was performed in human coronary EC and VSMC co-cultures across transwell inserts (in vitro MEJs) and in the intact mouse coronary circulation. Human coronary VSMC Notch activity induced by human coronary ECs at the in vitro MEJ was assessed using a CBF-luciferase construct. We observed Jagged1, Notch1, Notch2, and Notch3 expression within the in vitro and in vivo MEJs. We also demonstrated a 3-fold induction (p<0.001) of human coronary VSMC Notch signaling by ECs at the in vitro MEJ, which was completely blocked by the Notch inhibitor, DAPT (p<0.01). Conclusions: We demonstrate for the first time in mature blood vessels that Notch receptors and ligands are expressed within and are active at coronary MEJs, demonstrating a previously unrecognized mode of Notch signaling regulation between the endothelium and smooth muscle.